1983
DOI: 10.1042/bj2150539
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of the mycobacillin-synthesizing enzyme system

Abstract: The mycobacillin-synthesizing enzyme system was highly purified by fractionation at 30-55% (NH4)2SO4 saturation. The enzyme concentrate on Sephadex G-200 gel chromatography was resolved into three distinct fragments. Each of the fragments on further purification by DEAE-cellulose ion-exchange chromatography behaved as a single-component system, as clearly indicated by the sharpness of the peaks in the elution diagram. None of the fragments alone nor any two of them in all possible combinations possessed mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The incubation mixture and the method of isolation of radioactive mycobacillin were the same as described by Ghosh et al (1983), and that the radioactive material was mycobacillin was further confirmed by silica-gel t.l.c (Kieselgel F 1500;Schleicher und Schiill, Dassel, Germany) with the solvent system propanol/conc. NH3 (2:1, v/v), the radioactivity in the scraped material being found in the range of the RF value of authentic mycobacillin.…”
Section: Identification Oj Mycobacillin Formed By the Enzyme Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incubation mixture and the method of isolation of radioactive mycobacillin were the same as described by Ghosh et al (1983), and that the radioactive material was mycobacillin was further confirmed by silica-gel t.l.c (Kieselgel F 1500;Schleicher und Schiill, Dassel, Germany) with the solvent system propanol/conc. NH3 (2:1, v/v), the radioactivity in the scraped material being found in the range of the RF value of authentic mycobacillin.…”
Section: Identification Oj Mycobacillin Formed By the Enzyme Fractionsmentioning
confidence: 99%
“…The producer organism B. subtilis B3 (Majumder & Bose, 1958) The exchange was studied by using the method of Stulberg & Novelli (1960) as described by Ghosh et al (1983).…”
Section: Preparation Of Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Cell-free extracts of the strains were prepared and treated with (NH,),SO,. The precipitate collected between 30% and 55% saturation (Ghosh et al, 1983) was dissolved in buffer (50 mM-Tris/HCl pH 7.2, containing 0.25 mM-EDTA, 10 mM-MgCl, and 1 mM-DTT) and dialysed for 10 h against 2 litres of the same buffer, and used as a source of the enzyme. The incubation mixture (2 ml) used for the synthesis of peptides contained 5 mg enzyme, 100 pmol Tris/HCl buffer pH 7.2.…”
Section: E T H O D Smentioning
confidence: 99%
“…The present communication describes the isolation of some mycobacillin-negative: mutants from an auxotrophically tagged mutant of the producer B. subtilis B3 and the use of thew blocked mutants in whole-cell fermentation and cell-free in vitro synthesis, both to isolate and characterize some peptides that might be involved in mycobacillin biosynthesis, and to locate the enzyme defect in the three fractions (Ghosh et al, 1983) of the mycobacillin synthetase complex.…”
mentioning
confidence: 99%